The hybridization of media texts as a trend of the transformation of modern journalism - Korochenskiy, Aleksandr P. (Journal of the Belarusian State University. Journalism, 2019)
The modern journalism goes through deep transformations under the influence of commercialism and technological revolution. The actual trend was described as the hybridization of media texts, represented as journalistic product, with PR, commercial promotion and entertainment. The adoption of practices contrasting with traditional journalistic standards determined as the degeneration of journalism resulting the crisis of confidence to mass media.